2004
DOI: 10.1007/s00436-004-1250-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characteristics of the sporogenesis of genus Myxobolus infecting some Nile fishes in Egypt

Abstract: This study presents the ultrastructural characteristics of sporogenesis in the genus Myxobolus which infects four economically important Egyptian fishes: Oreochromis niloticus niloticus, Barbus bynni, Labeo niloticus and Hydrocynus forskalii, specimens of which were collected at Giza city. Although the cysts were observed in different organs, the pattern of sporogenesis was the same. Moreover, the sporogenesis found in the present study followed the usual pattern valid for most of the myxosporean genera studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…Nevertheless, the pericyte may be instrumental in several other aspects of this complex process, involving several cells which undergo differentiation, all within another cell. It is possible that the pericytes supply essential nutrients to the sporont progeny and that they may also supply molecular regulators which control sporogenesis (Current and Janovy 1978;Current et al 1979;Abdel-Ghaffar et al 2005) and all these characteristics and events are in agreement with the presented results herewith.…”
Section: Sporogenesissupporting
confidence: 91%
“…Nevertheless, the pericyte may be instrumental in several other aspects of this complex process, involving several cells which undergo differentiation, all within another cell. It is possible that the pericytes supply essential nutrients to the sporont progeny and that they may also supply molecular regulators which control sporogenesis (Current and Janovy 1978;Current et al 1979;Abdel-Ghaffar et al 2005) and all these characteristics and events are in agreement with the presented results herewith.…”
Section: Sporogenesissupporting
confidence: 91%
“…The plasmodium wall can supply various developing stages obtaining suitable nutrients necessary for growth via the pinocytotic canals which may incorporate host cell cytoplasm by pinocytosis. These findings are in agreement with other studies (Schubert 1968;Current and Janovy 1976;Desser and Paterson 1978;Abdel-Ghaffar et al 2005).…”
Section: Discussionsupporting
confidence: 96%
“…The later divided until they reached the five-cell stage. The differentiation of the sporont progenesis into spore-producing units occurred as rapid as in several other myxosporeans (Lom and de Puytorac 1965;Abdel-Aziz 1990;El-Mansy and Bashtar 2002;Abdel-Ghaffar et al 2005. Capsulogenesis Cheisin et al (1961) showed that the polar capsule has a spherical or elongated shape and contained an inverted polar filament; the walls of which were continuous with the walls of the capsular primordium.…”
Section: Sporogenesismentioning
confidence: 96%
“…(Vita et al 2003;Adriano et al 2005;Abdel-Ghaffar et al 2005;Azevedo et al 2008;Quraishy et al 2008). The desmosome-like junctions between two valvogenic cells in the present myxosporeans prove the generally accepted viewpoint that Myxozoa are multicellular animals (Siddall et al 1995).…”
Section: Discussionmentioning
confidence: 99%